2012
DOI: 10.1159/000334948
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Cochlear Microphonics at High Sound Pressure Levels as an Important Clinical Aspect

Abstract: Introduction: Cochlear microphonics are electrical stimulus responses of the inner ear, generated by mechanical displacement of the hair cells caused by acoustic stimulation. As cochlear microphonics are often used in the diagnosis of hearing impairment and deafness, in preliminary investigations it was seen that obliteration or ossification have no effect on the extent to which cochlear microphonics can be recorded at high sound pressure levels. As artifacts at high sound pressure levels suggested, measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Fibrous tissue growth that destroys cochlear tissue can be rapid with meningitis, so a negative ECoG is not unexpected. Recently, it has been reported that some patients with meningitis produce ECoGs (28), but these are apparently artifacts because with the same set-up similar results were obtained from saline-soaked drapes (29). It is not yet clear what the source of the artifact might be in those recordings, but in our recordings clamping of the sound tube virtually eliminated all responses.…”
Section: Discussionmentioning
confidence: 82%
“…Fibrous tissue growth that destroys cochlear tissue can be rapid with meningitis, so a negative ECoG is not unexpected. Recently, it has been reported that some patients with meningitis produce ECoGs (28), but these are apparently artifacts because with the same set-up similar results were obtained from saline-soaked drapes (29). It is not yet clear what the source of the artifact might be in those recordings, but in our recordings clamping of the sound tube virtually eliminated all responses.…”
Section: Discussionmentioning
confidence: 82%
“…Especially with stimulation levels of 80 dB normal hearing level (nHL) and more there is a certain possibility for false positive responses which was investigated, for example, by Teschner, Lenarz, and Battmer (2012) using a transtympanic needle electrode. Here ECochG recordings were performed on a wet flannel and a pumpkin with a stiff needle electrode.…”
Section: Introductionmentioning
confidence: 99%
“…When the electrode was placed too close to the stapes at the oval window, the oscillations of the incoming sound waves also led to movement of the recording electrode and, in turn, to oscillation of the impedance between the recording electrode and recording site. Thus, an artifact that looks very similar to the recorded response signal is induced, especially at stimulation levels from 80 dB nHL upward, such that the two are virtually indistinguishable ( Teschner, Lenarz & Battmer, 2012 ). Attempts have been made to remedy this by using cotton wick electrodes, in which the tip of the metal electrode is wrapped in wet medical cotton ( Calloway et al, 2014 ; Haumann et al, 2019 ; Mandalà, Colletti, Tonoli & Colletti, 2012 ).…”
Section: Introductionmentioning
confidence: 99%